Hemoglobin: Modification, Crystallization, Polymerization (Review) - V. A. Sergunova; E. A. Manchenko; O. Ye. Gudkova (Общая реаниматология, 2017)
The purpose of this review is to present the most significant modifications and transformations of a hemoglobin molecule potentially related to developing a strategy of resuscitation and treatment of lifethreatening forms of anemia. Hemoglobin is one of the wellstudied proteins. The paper reviews the history of hemoglobin studies from 1839 untill present. Methodically, the hemoglobin studies included electrophoresis, spectrophotometric method, Xray diffraction method, atomicforce microscopy. The basic forms of hemoglobin include oxyhemoglobin, deoxyhemoglobin and methemoglobin. Data on protein crystallization and polymerization are discussed. Many forms of hemoglobin have the ability to form crystals or polymers in vitro, some pathological forms can be modified in vivo. The studies of structural features of various hemoglobin forms represent a contemporary task for fundamental researches.